Tinjauan Fatwa DSN-MUI Nomor 06/DSN-MUI/IV/2000 terhadap Akad Istishna’ di Perumahan Syariah Alfarez Tasikmalaya - Munawaroh; Sandy Rizki Febriadi; Ira Siti Rohmah Maulida (Bandung Conference Series: Sharia Economic Law, 2022)
Abstract. Alfarez Housing is one of Sharia housings in Tasikmalaya, in the transaction using an istishna contract. The istishna’ contract has been regulated in the Fatwa DSN-MUI Number 06/DSN-MUI/IV/2000. However, in the transaction there are still several points that have not been implemented from the Fatwa DSN-MUI Number 06/DSN-MUI/IV/2000 concerning the istishna’ contract. The purpose of this study is to find out how the Fatwa DSN-MUI Number 06/DSN-MUI/IV/2000 reviews the istishna' contract in Alfarez Syariah Housing. This research uses qualitative research methods with a case study research approach. The types of research data are field data, research data sources are primary data sources and secondary data sources, data collection techniques are observation, interviews, and documentation. Then analyzed using descriptive analysis method. The results of this study conclude that in practice the istishna' contract that occurs in the Alfarez Tasikmalaya Syariah Housing there are still points that have not been implemented from the Fatwa DSN-MUI Number 06/DSN-MUI/IV/2000 regarding the istishna' contract, namely at the point of time and place of delivery of goods. must be determined by agreement. In practice, the time of delivery of goods is not in accordance with the agreement, there is a delay in the handover of keys/houses with the buyer and at the point the buyer (mustashni') is not allowed to sell goods before receiving them, but at Alfarez Syariah Housing it is allowed to sell the ordered house before the construction process is complete. Abstrak.Perumahan Syariah Alfarez Tasikmalaya adalah salah satu perumahan yang ada di Tasikmalaya, dalam transaksinya menggunakan akad istishna’. Akad istishna’ telah diatur dalam Fatwa DSN-MUI Nomor 06/DSN-MUI/IV/2000. Tetapi dalam transaksinya masih ada beberapa point yang belum terimplementasikan dari Fatwa DSN-MUI Nomor 06/DSN-MUI/IV/2000 tentang akad istishna’. Tujuan penelitian ini yaitu untuk mengetahui bagaimana tinjauan Fatwa DSN NOMOR 06/DSN-MUI/IV/2000 terhadap akad istishna’ di Perumahan Syariah Alfarez. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan penelitian studi kasus. Jenis data penelitiannya yaitu data lapangan, sumber data penelitian yaitu sumber data primer dan sumber data sekunder, teknik pengumpulan data yaitu observasi, wawancara, dan dokumentasi. Selanjutnya dianalisis dengan menggunakan metode analisis deskriptif. Hasil penelitian ini menyimpulkan bahwa dalam prakteknya akad istishna’ yang terjadi di Perumahan Syariah Alfarez Tasikmalaya masih ada point-point yang belum terimplementasikan dari Fatwa DSN NOMOR 06/DSN-MUI/IV/2000 tentang akad istishna’ yaitu pada point waktu dan tempat penyerahan barang harus ditetapkan berdasarkan kesepakatan. Dalam pelaksanaannya waktu penyerahan barang tidak sesuai dengan kesepakatan, terjadinya keterlambatan dalam serah terima kunci/rumah dengan pembeli dan dalam point pembeli (mustashni’) tidak boleh menjual barang sebelum menerimanya tetapi di Perumahan Syariah Alfarez diperbolehkan menjual rumah yang dipesan sebelum proses pembangunan selesai